PENGUATAN LITERASI MEDIA SISWA DALAM PEMBELAJARAN EKONOMI - Milawati; Marini, Sylvi (CENDIKIA, 2021)
The media literacy movement into the world of educationis important because our students are from the Z generation in the technology and infromation age. The aims of this study is to analyze strengthening student media literacy in economic learning. The data collection methode in this study was explored through literature review. The result show that the strengthening students’ media literacy in learning education can be done by integrating learning media or assigning students with media news sources that must be sought independently by children.